Modernization of Islamic Boarding School Education: Balancing Tradition and Contemporary Demands - Ahmad Qurtubi (Al-Qalam Institue, 2026)
This study aims to analyze the modernization policy of Islamic boarding school education and how it balances the preservation of traditional values with contemporary educational demands. A qualitative approach was employed using a library research method, drawing on scholarly articles, academic books, and relevant policy documents. The findings reveal that modernization in Islamic boarding schools involves curriculum integration between religious and general subjects, innovation in teaching methods, enhancement of institutional management, and the adoption of digital technologies in learning processes. Despite these developments, traditional elements such as the study of classical Islamic texts and the central role of religious scholars remain integral to the educational system. The study implies that modernization policies are essential for strengthening the adaptability and sustainability of Islamic educational institutions. From an educational management perspective, effective integration of innovation and tradition can enhance institutional performance while preserving core values, ensuring that Islamic boarding schools remain relevant in a rapidly changing educational landscape.